Adaptation of climate change: Sustainable tourism development - Cemara, Gita; Ismail, Yunita (Ecotourism and Environment Conservation, 2024)
Background: Climate change refers to rapid changes of natural phenomena like weather patterns that are not caused by natural causes. Tourism sector shows its vulnerability to climate change remembering that this sector really depends on the climate condition. This paper aims to explore the vulnerability of tourism to climate change, tourism under climate change scenarios, and tourism adaptation to climate change using literature review method. This paper also includes the estimation on global impact of climate change tourism industry. Many researchers agreed that a solid framework needs to be established as an effort to adapt and mitigate climate change. One form of effort to achieve this is by environmental education, provision of loans, green tourism, eco-tourism, and environmental conservation projects. Nevertheless, this is not an all-fit in solutions, further research needs to be established to build a solid framework that involves all stakeholders. Methods: This paper is arranged using a literature review method sherached from many resources on the internet. The tourism vulnerability is really affected by climate change. Findings: This paper aims to explore vulnerability of tourism to climate change, tourism under climate change scenarios, and tourism adaptation to climate change. Conclusion: The tourism industry requires many sources of energy such as water, electricity, fossil fuel, etc., hence evaluating the system and framework is important to keep the sustainability and its resilience to climate change.